A formação do Tradutor Juramentado - Santos, Orlanda Miranda (Language and Law / Linguagem e Direito, 2016)
This article offers a reflection on the training of Certied Translators (CT), focusing especially on the legal arena, and presents the ndings of a project that is currently being developed in the area. In Brazil, a CT is an individual that translates public documents whose translation is legally required in the country. That individual will have been examined, but has no employment relationship with the State. No academic qualication or professional training is required in order to be a CT. In addition to providing an explanation of the requirements underlying the public examination of a CT and some theories of Translation Studies, this research presents a project that aims to collect a parallel corpus and analyze the trends of translation of legal terms, in order to assist the translator in translating these terms between the pairwise Portuguese/Spanish. According to Ulsh (1971: 10), more than 85% of the Portuguese vocabulary – and especially the lexicon – are likely to have Spanish cognates. The translator must be careful enough to search for terms in context, rather than trust the strong similarities between the two languages.